Current status of diagnosis and treatment of hepatic echinococcosis - Mihmanli, Memmet; Idiz, Ufuk Oguz; Kaya, Cemal; Demir, Uygar; Bostanci, Ozgur; Omeroglu, Sinan; Bozkurt, Emre (World journal of hepatology, 2016)
Echinococcus granulosus(E.granulosus) and Echinococcus multilocularis(E.multilocularis) infections are the most common parasitic diseases that affect the liver.The disease course is typically slow and the patients tend to remain asymptomatic for many years.Often the diagnosis is incidental.Right upper quadrant abdominal pain,hepatitis,cholangitis,and anaphylaxis due to dissemination of the cyst are the main presenting symptoms.Ultrasonography is important in diagnosis.The World Health Organization classification,based on ultrasonographic findings,is used for staging of the disease and treatment selection.In addition to the imaging methods,immunological investigations are used to support the diagnosis.The available treatment options for E.granulosus infection include open surgery,percutaneous interventions,and pharmacotherapy.Aggressive surgery is the first-choice treatment for E.multilocularis infection,while pharmacotherapy is used as an adjunct to surgery.Due to a paucity of clinical studies,empirical evidence on the treatment of E.granulosus and E.multilocularis infections is largely lacking;there are no prominent and widely accepted clinical algorithms yet.In this article,we review the diagnosis and treatment of E.granulosus and E.multilocularis infections in the light of recent evidence.